Menstrual characteristics in Korean women with endometriosis: a pilot study - Ji Yeon Han; Eun Ji Lee; Byung Chul Jee; Seok Hyun Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThis study aimed to determine whether the menstrual characteristics are different in Korean women with or without ovarian endometrioma.MethodsWe selected 95 premenopausal women aged below 39 years who underwent laparoscopic surgery for ovarian endometrioma (n=46) or other benign ovarian tumors (n=49) between April 2016 and February 2017. We excluded those with uterine diseases that could potentially affect the menstrual characteristics and those on anticoagulants or hormonal medication. At admission, menstrual characteristics such as cycle length, cycle regularity, and menstrual duration, were collected. In addition, amount of menstrual bleeding and severity of dysmenorrhea were recorded using a pictorial blood loss assessment chart (PBAC) and visual analogue scale, respectively.ResultsAge and parity were similar in both women with ovarian endometrioma and women with other benign ovarian tumors. Body mass index (BMI) was significantly lower (median, 20.9 vs. 22.1 kg/m2; P=0.031) in women with ovarian endometrioma. The amount of menstrual bleeding (median PBAC score, 183 vs. 165), menstrual duration (median, 6 vs. 6 days), and cycle length in women with regular cycle (median, 29.0 vs. 29.2 days) were not different between the 2 groups. Pain score was significantly higher (median, 4 vs. 3; P=0.005) in women with ovarian endometrioma.ConclusionWe found that the menstrual characteristics between women with ovarian endometrioma and women with other benign ovarian tumors were similar. We also observed that low BMI may be one of the risk factor for endometriosis.